Acculturative Stress and Life Satisfaction of Immigrant Vietnamese Wives Living in South Korea: The Moderating Role of Intimate Partner Violence - Vo, Nhat Huy (Journal of interpersonal violence, 2022)
This study examined the relationships between acculturative stress, intimate partner violence (IPV), and life satisfaction of immigrant Vietnamese wives. A total of 288 immigrant Vietnamese women who were married to Korean men and were living in South Korea participated in the survey. As expected, the results indicated that acculturative stress was negatively related to life satisfaction. Moreover, IPV significantly moderated the relationship between acculturative stress and life satisfaction. The moderating role of IPV is evident when the acculturative stress is low.